Teknologi Versus Superstition Dalam A Connecticut Yankee in King Arthur’s Court Karya Mark Twain: Sebuah Kajian The Expressive Theory Of Art - Murti Heruri (Dinamika Bahasa dan Budaya, 2015)
Novel A Connecticut Yankee in King Arthur’s Court is a serious novel written by Mark Twain which was equal in power to Huckleberry Finn, his masterpiece novel. This research attempts to show sets of values between the old world and the new world. One of the values is “Technology versus Superstition”. The novel focused on Hank Morgan, a Superintendent at the Harford Colt Arms Factory, who tried to in vain to impose his 1880s American mind on the feudal society of Arthurian England in the sixth century.In undertaking study, the theoretical approach is Reception Theory. Reception Theory says the reader takes an active part in the literary process and gives meaning to the work of art itself. However, to prevent the analysis from becoming subjective, The Expressive Theory of Art is applied. The choice is that A Connecticut Yankee in King Arthur’s Court is a bitter satirical piece of writing by Twain who, in his declining years, turned more and more pessimistic about American Society. This study is in the hope of allowing the readers to know the grains of truth in this novel and thus broaden our literary vistas. Key words: technology, superstition, the old world (1880s), the new world (17th Century)